TINGKAT PERCAYA DIRI SISWA KELAS X KKKR DALAM PEMBELAJARAN SEPAKBOLA DI SMKN 4 PEKANBARU - Rices Jatra; Soleh Hadi; Mimi Yulianti; Nova Risma (Journal of Physical Activity and Sports (JPAS), 2026)
The purpose of this study was to determine the confidence level of Grade X KKKR students in football learning at SMKN 4 Pekanbaru. This research is a descriptive quantitative study. The population and sample of the study consisted of 30 Grade X KKKR students involved in football learning at SMKN 4 Pekanbaru. The research instrument used was a questionnaire with a Likert scale, which was then processed using a percentage formula. Based on the research data obtained from 11 indicators of student confidence level, the average percentage was 83.56%. Referring to the percentage score criteria, this figure falls within the range of 81% – 100%, which is categorized as "Very Strong". The conclusion of this study is that Grade X KKKR students have excellent self-confidence in football learning, covering mental, social, and emotional aspects, which provides a positive impact on their learning process and outcomes